Exclusive and concurrent use of cigarettes and alternative tobacco products among Hong Kong adolescents - Jiang, Nan (Tob Prev Cessat, 2018)
INTRODUCTION: The use of alternative tobacco products (ATPs) is becoming increasingly popular among the youth. This study aimed to assess cigarette-only smoking, exclusive ATP use, and concurrent use (cigarettes and ATPs) among adolescents in Hong Kong. METHODS: We analyzed data of the Hong Kong School-based Survey on Smoking among Students 2012/13 from a representative sample of 45 857 secondary school students. Weighted prevalence of cigarette-only smoking, exclusive ATP use, and concurrent tobacco use were calculated. Multinomial logistic regression examined correlates of exclusive ATP use and concurrent use relative to cigarette-only smoking. Among current (past-30-days) cigarette smokers, multivariable logistic regression assessed whether ATP use was associated with nicotine dependence, quit intention and quit attempt. RESULTS: Overall, 5.8% of adolescents reported current tobacco use (2.1% cigarette-only smoking, 2.5% exclusive ATP use and 1.2% concurrent use). Compared with cigarette-only smoking, exclusive ATP use and concurrent tobacco use were associated with younger age, higher perceived family financial status, absence of cigarette smoking peers, poor knowledge about smoking and more frequent alcohol use. Among current cigarette smokers, ATP use was negatively associated with cigarette quit intention and quit attempt. CONCLUSIONS: ATP use was as prevalent as cigarette smoking among adolescents, and ATP users were different from cigarette smokers in many demographic and psychosocial factors. Tobacco control programs among youth should target different types of tobacco users and address all forms of tobacco products.